The importance of identifying preferred place of death. Issue 1 (25th September 2015) - Ali, Maimoona; Capel, Margred; Jones, Gareth; Gazi, Terri
Abstract : Objectives: The majority of people would prefer to die at home and the stated intentions of both statutory and voluntary healthcare providers aim to support this. This service evaluation compared the preferred and actual place of death of patients known to a specialist community palliative care service. Design: All deaths of patients (n=2176) known to the specialist palliative care service over a 5-year period were examined through service evaluation to compare the actual place of death with the preferred place of death previously identified by the patient. Triggers for admission were established when the patients did not achieve this preference. Results: Between 2009 and 2013, 73% of patients who expressed a choice about their preferred place of death and 69.3% who wanted to die at home were able to achieve their preferences. During the course of their illness, 9.5% of patients changed their preference for place of death. 30% of patients either refused to discuss or no preference was elicited for place of death. Conclusions: Direct enquiry and identification of preferences for end-of-life care is associated with patients achieving their preference for place of death. Patients whose preferred place of death was unknown were more likely to be admitted to hospital for end-of-life care.